The infectious laryngotracheitis in Greece. Immunization against the disease by vaccine administered by the drinking water in the field - MENALE, Ι.; ΣΕΪΜΕΝΗΣ, Α.; ΛΟΥΚΑΣ, Σ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The authors present the results of field trials on vaccination against L. T. by modified attenuated live virus vaccine, via the drinking water. This study was undertaken in the region of Eubea, during the period of 1971 and 1972, where the disease appeared in a severe form and in the beginning of 1977 in an infected poultry farm of the same region. A total of 203.000 broiler and reproduction chickens were involved. It was demonstrated that this route of administration was as efficient as the ocular one even in a heavely contaminated area. The bigest advantage of this method is the rapid and economical mass-vaccination thus avoiding the handling of individual birds.